Evaluation of Serum Soluble fms-like Tyrosine Kinase-1 as a Biomarker in Ectopic Pregnancy - Alaa Raeed; Aseel Ghazi Rifat (University of Kirkuk, College of Medicine, Kirkuk, Iraq, 2024)
Background: An ectopic pregnancy occurs when a blastocyst implants outside the uterine, early diagnosis is crucial for minimizing associated risks. Soluble FMS-like tyrosine kinase1 (sFlt-1) is the soluble variant of the vascular endothelial growth factor receptor1 that forms a barrier against abnormal vascular permeability and abnormal angiogenesis. Thestudy aims to determine the level of (sFlt-1) in ectopic pregnancy and identify whether it can be used as a biomarker to distinguish ectopic from normal intrauterine pregnancy and missed miscarriage.Methods: A prospective case-control study enrolled 90 pregnant women, with gestational age (4-10 weeks) divided into three groups: 30 women with ectopic pregnancy, 30 missed miscarriages, and 30 women with normal intrauterine pregnancy. (sFlt-1) was measured and statistical analysis of the data was performed to compare the level of biomarkerbetween the studied groups.Results: The mean level of (sFlt-1) was significantly lower among ectopic pregnancy (0.25 ± 0.07 ng/ml) in comparisonto miscarriage and intrauterine pregnancy group. The (sFlt-1) at a level of 0.277 ng/ml was able to distinguish an ectopic pregnancy from normal intrauterine pregnancy and miscarriage with a sensitivity of 90% and a specificity of 70%. The mean serum (sFlt-1) increased with increasing gestational age, especially at more than 8 weeks.Conclusion: A single measurement of the level (sFLt- 1) level can efficiently discriminate ectopic pregnancy from viable and non-viable intrauterine pregnancy. Serum (sFLt-1) at the cut-off value had the same sensitivity and better specificity than βhCG in the diagnosis of ectopic pregnancy.